Retract: Media Sosial sebagai Ruang Baru Kekerasan Berbasis Gender Online di Indonesia - Bambang Arianto (Universitas Islam Malang, 2021)
This article aims to elaborate on the phenomenon of Online Gender Based Violence (KBGO) during the Covid-19 (Covid-19) pandemic. The Covid-19 pandemic has led to a transformation of lifestyle from conventional to digital-based. In addition to the positive impact, digital transformation has created a negative impact, namely helping to strengthen the practice of online gender-based violence on social media. The lack of digital literacy and the opening of opportunities have influenced the spread of online gender-based violence practices on social media. This study uses an explanatory qualitative research method through in-depth interviews. This article states that anticipatory steps are needed as an effort to prevent this practice including; First, strengthening digital literacy, especially for the millennial generation. Second, build a networked digital community. Third, the involvement of men for early detection and prevention. Finally, the government's role is needed to create regulations that can eradicate the practice of online gender-based violence.